1999
DOI: 10.1109/10.752941
|View full text |Cite
|
Sign up to set email alerts
|

A high-temporal resolution algorithm for quantifying organization during atrial fibrillation

Abstract: Atrial fibrillation (AF) has been described as a "random" or "chaotic" rhythm. Evidence suggests that AF may have transient episodes of temporal and spatial organization. We introduce a new algorithm that quantifies AF organization by the mean-squared error (MSE) in the linear prediction between two cardiac electrograms. This algorithm calculates organization at a finer temporal resolution. (approximately 300 ms) than previously published algorithms. Using canine atrial epicardial mapping data, we verified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 50 publications
9
78
0
Order By: Relevance
“…This observation agrees with findings reported in other works, such as: (i) the higher the AA organization, the higher the success rates in AF cardioversion [24,11], (ii) the higher the level of AA organization, the lower the energy required for successful cardioversion [12] and (iii) paroxysmal AF requires less energy for cardioversion than persistent AF [25]. These previous observations highlight the fact that, when a higher number of reentries are wandering throughout the atrial tissue, a lower probability of successful electrical cardioversion is obtained.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This observation agrees with findings reported in other works, such as: (i) the higher the AA organization, the higher the success rates in AF cardioversion [24,11], (ii) the higher the level of AA organization, the lower the energy required for successful cardioversion [12] and (iii) paroxysmal AF requires less energy for cardioversion than persistent AF [25]. These previous observations highlight the fact that, when a higher number of reentries are wandering throughout the atrial tissue, a lower probability of successful electrical cardioversion is obtained.…”
Section: Discussionsupporting
confidence: 93%
“…This observation also agrees with the outcomes reported with invasive recordings [24,11] and, thereby, the obtained results consistency is increased.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although previously thought to be a "random" arrhythmia, animal and human studies have shown various degrees of spatiotemporal organization during sustained AF. [1][2][3][4][5][6] In humans, Haissaguerre and colleagues 7 showed that the onset of AF is frequently triggered by atrial premature beats that originate from sleeves of atrial muscle that extend into the pulmonary veins (PVs). Others have reported focal firing within the PVs during sustained AF.…”
mentioning
confidence: 99%